Women directors' board involvement and remuneration matter for performance of Malaysian listed healthcare companies? A comparison before and during Covid-19 - Sijess Hong; Peck-Ling Tee; Hui-Wen Mok; Jia-Ru Lee; Jin-Mei Huang; Vivien Ming-Zhu Tan (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
Most Malaysian listed companies have yet to achieve the government’s target of 30% women holding senior management roles, unlike the rising trend observed across regions. Moreover, glass cliff theory as opposed to female leadership theory showed empirical evidence that associate women directors with poor corporate performance as they are hired either to comply with the quota stipulated by government authorities or as a scapegoat for unavoidable business failure during crisis period. Besides, empirical evidence of gender pays disparity also demotivated women directors and consequently ramified corporate performance. An overall panel of 87 firm-year observations compiled from 24 listed healthcare companies from 2018 to 2021 are used to test whether percentage of women directors (WDIR), ratio of average women to men directors’ remuneration (WREM), average age of women directors (WAGE), woman chairman dummy (WCHM) and woman CEO dummy (WCEO) affect return on equity (ROE). Random effect regression model results show that WCHM negatively affect ROE in the overall panel (2018-2021) and WAGE positively affect ROE in the during Covid sub-panel (2020-2021). Except for these, women directors’ board involvement and remuneration are generally insignificant in influencing healthcare companies ROE because women are under-represented on boards in this sector (mean WDIR of 23.27%), women directors are underpaid in comparison to their men counterparts (mean WREM of 0.8920 which is less than 1) and many of the companies listed in this sector are still relatively new.